The Role of Sudanese Depression in Snowfall on Baghdad City (dated 11/1/2008): The Role of Sudanese Depression in Snowfall on Baghdad City (dated 11/1/2008) (Journal of the College of Education for Women, 2019)
AbstractOn 11/1/2008 amounts of snows fell on various sections of Iraq, one ofwhich is Baghdad. The analysis process of climatic maps proved that theadvance trough of Sudanese depression towards the city is the reason behindthe formation of this weather state supported by could trough in the (500) mbpressure level. .The research concluded that the phenomenon of global warmingwitnessed by the world recently had a main role in the occurrence of thisphenomenon due to the raise in earth temperature as a result of evaporationrate increase leading to an increase in water vapor and cloud formation withhigh tops and low bases which form sows with high rates accumulating at highand moderate latitudes leading consequently to the increase of air massescoldness laying down over extensive ice covers in those latitudes which theireffect reach to our areas.